TRANSFORMATIONAL PROCESSES IN ADULT EDUCATION IN THE REPUBLIC OF POLAND - Maria Yaremchuk (Borys Grinchenko Kyiv Metropolitan University, 2024)
The article discusses the transformational processes in adult education in the Republic of Poland. The normative legal documents that influenced the education of adults are analyzed; documents in the field of adult education, resolutions introduced for the period of temporary restriction of the functioning of units of the education system, in particular higher education institutions and other educational institutions, as well as employers, in connection with the prevention, counteraction and fight against COVID-19. It is concluded that, depending on the epidemic situation, online classes, hybrid or stationary classes were limited or cancelled, which affected both the organization of the educational process of adult learning, and its participants. Classes using distance learning methods and techniques have become a priority. The transformational processes in adult education in the Republic of Poland allow us to conclude that there is a clear relationship between adult education and change. Polish andragogues in their reflections and studies draw attention to this relationship. Attention is drawn to the fact that there is a double impact of transformations on adult education: the goal of transformation is not only to reduce the tension that led to the transformation, but also to create new conflicts that should stimulate the individual to creative activity in this new situation It is also necessary to pay attention to the dual impact of the transformation of the system on adult education: it is always stated that its purpose is not only to reduce tension, which led to transformation, but also to the creation of new conflicts that should stimulate the individual to creative activity in this new political formation. The forms and content of adult education today are determined by three vectors: the needs of the labor market, the resources and capabilities of the modern information society, and the individual aspirations of adults for education. The synergistic effect of the interaction of these vectors may be a change in the way of perception and organization of educational processes for adults, which will lead to a decrease in their institutionalization.